Positive calretinin stain with immunohistochemistry in a 49 year-old female with cardiac myxoma: A case report - I Gusti Ayu Sri Mahendra Dewi (Intisari Sains Medis, 2020)
Background: Primary tumors of the heart are scarce. Cardiac myxoma is a primary benign heart tumor most often found with an incidence of 0.5-1.0 cases per million population per year and 90% diagnosed in the fourth to seventh decades of life, rarely found in children. Cardiac myxoma is three times more common in women than in men. These tumors are mostly found in the left atrium.Case description: Female, a 49-year-old patient, came with palpitations, shortness of breath, and weakness since the previous six months. On echocardiography, found a mass in the left atrium suspected of a left atrial myxoma. Surgery was performed, and the specimen was sent for histopathological examination. Macroscopically, the tumor mass shows an irregular shape, brownish color, and spongy consistency. Microscopic examination shows the tumor consisting of proliferation of spindle-shaped and stellate cells, with oval to round nuclei, eosinophilic cytoplasm, mostly scattered, some of which are arranged cord and nest, infiltrative between the myxoid stroma and partially surround small blood vessels to form a vasoformative ring. The specimen also contains the proliferation of blood vessels, extravasation of erythrocytes, and the distribution of inflammatory cells and hemosiderophages. The result of the immunohistochemical examination with calretinin was positive.Conclusion: This case was concluded as cardiac myxoma based on clinical features, echocardiography, macroscopic, routine histopathological, and immunohistochemical examinations.